2014
DOI: 10.1007/s00705-014-2051-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on the extrinsic incubation period and infection rate of dengue virus serotype 2 infection in Aedes albopictus

Abstract: Dengue fever is an acute mosquito-borne viral disease caused by dengue virus (DENV). Temperature may affect the efficiency of the mosquito vectors in spreading DENV. Aedes albopictus mosquitoes were infected orally with a DENV2 suspension and incubated at different temperatures. Subsequently, DENV2 antigen was collected from salivary gland and thorax-abdomen samples on different days postinfection and tested using an immunofluorescence assay to determine the extrinsic incubation period and infection rate. As t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
79
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 26 publications
8
79
0
1
Order By: Relevance
“…albopictus in the winter [4], the occurrence of dengue epidemics in Guangzhou depends highly on imported cases from surrounding endemic countries, such as Thailand, Singapore, Malaysia, Philippines, Vietnam, Cambodia, and Indonesia. Serving as a transportation hub for these countries increases the outbreak risk of Guangzhou further (Fig 1C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…albopictus in the winter [4], the occurrence of dengue epidemics in Guangzhou depends highly on imported cases from surrounding endemic countries, such as Thailand, Singapore, Malaysia, Philippines, Vietnam, Cambodia, and Indonesia. Serving as a transportation hub for these countries increases the outbreak risk of Guangzhou further (Fig 1C).…”
Section: Methodsmentioning
confidence: 99%
“…Because of its warm and wet climate, as well as the close ties with dengue endemic Southeast Asian countries, Guangzhou has a high risk of local dengue transmission. The introduction of dengue virus (DENV) by imported cases is required annually for local epidemics in Guangzhou, since the dengue virus cannot disseminate to the salivary glands of Aedes albopictus when temperature is below 18°C [4] and adult mosquitoes rarely survive the winter.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings show that this association is mainly related to direct effects of temperature on dengue transmission rate. Mechanisms for such direct effects include, for example, temperature effects on the biting rate of mosquitoes (18), incubation period of pathogens (19), and human exposure to mosquitoes (e.g., by influencing the time spent outdoors or with open windows). In contrast, GAM results show no significant association of the temperature variables considered with mosquito population dynamics.…”
Section: Significancementioning
confidence: 99%
“…(a) climatic (and environmental: temperature, rainfall and humidity) factors as well as human behaviors (urbanization and globalization) and (b) overall lack of vector control measures and absence of anti-dengue antiviral as well as absence or limitation in usage of licensed dengue (only dengvaxia: CYD-TDV) vaccine [6][7][8][9]. DHF was first reported in Calcutta (Kolkata), West Bengal in 1963 and 1964 [10,11], and due to the co-circulation of all four DENV (DENV1, DENV2, DENV3 and DENV4) serotypes this region has been designated as hyper-endemic [12].…”
mentioning
confidence: 99%
“…Several dengue episodes hit Kolkata from time to time [13,14] The extrinsic incubation period (EIP: Time span for viral incubation between the ingestion of viremic blood from the human, by a mosquito vector, and detection of DENVs in the mosquito salivary glands for transmission to a new susceptible host) might explain the transmission dynamics of DENVs, and hence the dengue-preparedness for proper management [2]. It has been shown experimentally that at temperature <18°C, DENVs are not detected in the vector's (A. albopictus) salivary glands, while at 21°C, DENV antigens are detectable, and therefore, reports are aptly available on the decrease of EIP from 9 days (at 26°C) to 5 days (at 30°C), and 8 days to 15 days, respectively at 30.8°C and 23.4°C, suggesting the gradual increase of DEN incidences with increased temperature, peaking at ~ 32°C prior to declining at higher temperatures [2,6,7]. Watts et al [19] demonstrated in Ae.…”
mentioning
confidence: 99%